2019
DOI: 10.1111/aos.14225
|View full text |Cite
|
Sign up to set email alerts
|

Change in peripapillary and macular choroidal thickness change in children with type 1 diabetes mellitus without visual impairment or diabetic retinopathy

Abstract: Purpose To study the characteristics of choroid thickness (CT) of the optic disc and macula in children with type 1 diabetes mellitus (T1DM) without visual impairment and diabetic retinopathy (DR) and analyse associated factors. Methods A square area of 6 × 6 mm around the centre of the optic disc and macula was scanned. The indices analysed mainly included CT at the macular centre (1 mm), and temporal, superior, nasal or inferior aspect of the inner ring (1–3 mm) and outer ring of (3–6 mm) optic disc and macu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…All the children with diabetes were diagnosed with T1DM caused by the absolute lack of insulin, and blood glucose fluctuation was obvious and difficult to control; most of them had autoimmune diseases, and most had normal or reduced weight. In this study, no significant difference was observed in the BMI between children with diabetes and healthy controls, but choroidal thickening could occur in children with early diabetes (Li et al, 2020). We inferred this might increase the blood supply to the optic nerve tissue to some extent or slow the metabolism of RPE cells around the optic disc, making b-PPA area smaller in these children with diabetes than in healthy children.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…All the children with diabetes were diagnosed with T1DM caused by the absolute lack of insulin, and blood glucose fluctuation was obvious and difficult to control; most of them had autoimmune diseases, and most had normal or reduced weight. In this study, no significant difference was observed in the BMI between children with diabetes and healthy controls, but choroidal thickening could occur in children with early diabetes (Li et al, 2020). We inferred this might increase the blood supply to the optic nerve tissue to some extent or slow the metabolism of RPE cells around the optic disc, making b-PPA area smaller in these children with diabetes than in healthy children.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies also showed that an increase in b-PPA was significantly associated with a decrease in choroidal thickness (CT) (Sullivan-Mee et al 2015). In addition, we had found that the parapapillary CT in children with diabetes without DR or VI was larger than that in healthy control children (Li et al 2020).…”
Section: Discussionmentioning
confidence: 61%
“…This study was a part of the Shanghai Children and Adolescent DM Eye study (SCADE) (clinical trial registration number: NCT 03587948) [21], and it included two hospital-based surveys (conducted in 2019 and in 2021 separately). This study was conducted in accordance with the tenets of the Declaration of Helsinki, and was approved by the ethics committees of the Shanghai General Hospital a liated to Shanghai Jiao Tong University School of Medicine and Children's Hospital of Fudan University in Shanghai (approval number: 2016KY005 and LS No.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…Fieß et al ( 108 ) reported that premature birth itself does not affect peripapillary CT, however they found that infants born small for their gestational age had peripapillary choroidal thinning when compared to those infants born at the appropriate gestational age. Li et al ( 96 ) measured macular and parapapillary CT in children with diabetes and reported that inferior and nasal parapapillary CT were increased in children with type 1 diabetes and without retinopathy or visual impairment as compared to healthy controls. However, Ermerak et al ( 97 ) also showed that nasal and inferior peripapillary CT were lower in children with type 1 diabetes who had no retinopathy than in normal controls, although macular CT did not differ between the groups.…”
Section: Choroidal Thickness Measurement Beyond the Maculamentioning
confidence: 99%